Implicaciones del gobierno corporativo en las economías emergentes (2009)
This article, pretend to expose the behavior of the Latin American markets, which, as emerging economies, must give priority to the concept of good corporate governance to allow the growth of their companies, and avoid the corporate crisis. This paper also explain the right proceedings at the interior of societies, to achieve a satisfactory effect on the market